2012 European guideline for the management of pelvic inflammatory disease. (January 2014) - Ross, Jonathan; Judlin, Philippe; Jensen, Jorgen
This guideline was produced by the European region of the International Union against sexually transmitted infections (IUSTI) and refers to ascending infections in the female genital tract unrelated to delivery and surgery and does not include actinomyces-related infection.